Character Educational Values in The Movie “Turning Red” and its Implication Toward Character Education of Young Learners - Jehan Ayu Mentari; Masagus Firdaus; Hanni Yukamana (Journal on Education, 2024)
This case study looks at the function of movies in educational character, specifically the animated feature "Turning Red." Employing an expressive subjective strategy based on constructionism and basic speculations, the consider looks for to find the film's character instructive values and examine their results for youthful learners' character advancement. Essential sources are the characters' exercises, which are strengthened by auxiliary sources such as motion picture clips, discourses, and character ponders. The inquire about employments observational investigation, interviews with film specialists and onlookers, and substance examination of instructive character beliefs. Triangulation increments the research's legitimacy by pushing innovation implies for extricating information from the motion picture and its screenplay. The investigate reveals a different set of character educational standards encoded within the film's talk, activities, and intuitive. The ponder employments a categorization system to distinguish these values and analyze their results for students' character instruction. "Turning Red" develops as an viable instrument for instructing solid character characteristics and moral standards in youthful understudies, contributing to a more nuanced see of movies' multidimensional work in instruction and conceivable affect on character improvement.